Electrochemical Label‐Free Nucleotide Sensors. Issue 12 (4th September 2015) - Aoki, Hiroshi
Abstract: Numerous researchers have devoted a great deal of effort over the last few decades to the development of electrochemical oligonucleotide detection techniques, owing to their advantages of simple design, inherently small dimensions, and low power requirements. Their simplicity and rapidity of detection makes label‐free oligonucleotide sensors of great potential use as first‐aid screening tools in the analytical field of environmental measurements and healthcare management. This review article covers label‐free oligonucleotide sensors, focusing specifically on topical electrochemical techniques, including intrinsic redox reaction of bases, conductive polymers, the use of electrochemical indicators, and highly ordered probe structures. Abstract : Simpler and Faster ! Electrochemical label‐free sensors for the detection of oligonucleotides have been a focus of key research in past decades, and are likely to play an ever more important role in the analytical field (see figure). The benefits of electrochemical devices enable the fabrication of compact, low‐cost, and low‐energy‐requiring apparatus. Electrochemical label‐free oligonucleotide sensors have considerable potential for ubiquitous practical application in numerous fields.